2022
DOI: 10.1186/s12934-022-01878-2
|View full text |Cite
|
Sign up to set email alerts
|

Mnsod1 promotes the development of Pleurotus ostreatus and enhances the tolerance of mycelia to heat stress

Abstract: Background Superoxide dismutases (SODs, EC 1.15.1.1) are defense proteins that can be used as sweepers to clear reactive oxygen species (ROS). They have been widely studied in the plant. Intensive research demonstrates that SOD plays an essential role in plants. However, in Pleurotus ostreatus, the function and regulatory pathway of SOD in the growth and development and the abiotic stress response have not been clear. Results In this study, three M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that H 2 O 2 is abundant at the edge of colonies on PDA plates. It is speculated that the presence of H 2 O 2 may regulate the elongation of apical mycelia [ 38 ]. The results of this study showed that H 2 O 2 accumulated gradually during the transformation from mycelia to primordia in P. ostreatus ( Figure 6 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that H 2 O 2 is abundant at the edge of colonies on PDA plates. It is speculated that the presence of H 2 O 2 may regulate the elongation of apical mycelia [ 38 ]. The results of this study showed that H 2 O 2 accumulated gradually during the transformation from mycelia to primordia in P. ostreatus ( Figure 6 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…The OE-aox strain can actively respond to 32 • C heat stress in mycelium [22]. After being subjected to heat stress, strain OE-Mnsod1 has a faster mycelial recovery rate than the WT strain and participates in the mycelial heat stress reaction of P. ostreatus [27]. Therefore, determining whether pal1, pal2, aox, and Mnsod1 are regulated by PoMYB12, PoMYB15, or PoMYB20 and their involvement in the heat stress regulatory pathway warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Using the research method of Ludan Hou [27], the amplification of the hygromycin (Hyg) gene in P. ostreatus, transformed with the OE-PoMYB12 plasmid, was conducted (Figure S3a). Subsequently, the relative expression level of the PoMYB12 in the transformed strains was detected.…”
Section: Pomyb12 Pomyb15 and Pomyb20 Are Involved In The Response Of ...mentioning
confidence: 99%
“…Various substances, such as trehalose, salicylic acid (SA), and nitric oxide (NO), can enhance the ability of P. ostreatus to survive under HS by helping them maintain redox and metabolic homeostasis (Lei et al, 2019;Hou et al, 2020;Hu et al, 2022). Several metabolic enzymes, such as MnSOD1, PAL, aconitase, and alternative oxidase, can also help P. ostreatus cope with HS (Hou et al, 2019;Hou et al, 2020;Hou et al, 2021;Hou et al, 2022). In another study, we found that metabolism is rearranged under HS in P. ostreatus.…”
Section: Introductionmentioning
confidence: 97%